Consistent Abnormalities in Metabolic Patterns of Lewy Body Dementias. Issue 9 (20th July 2022) - Lu, Jiaying; Ge, Jingjie; Chen, Keliang; Sun, Yimin; Liu, Fengtao; Yu, Huan; Xu, Qian; Li, Ling; Ju, Zizhao; Lin, Huamei; Guan, Yihui; Guo, Qihao; et al.
ABSTRACT: Background: Whether dementia with Lewy bodies (DLB) and Parkinson's disease (PD) dementia (PDD) represent the same disease, distinct entities, or conditions within the same spectrum remains controversial. Objective: The objective of this study was to provide new insight into this debate by separately identifying disease‐specific metabolic patterns and comparing them with each other and with previously established PD‐related pattern (PDRP). Methods: Patients with DLB (n = 67), patients with PDD (n = 50), and healthy control subjects (HCs; n = 15) with brain 18 F‐fluorodeoxyglucose positron emission tomography were enrolled as cohorts A and B for pattern identification and validation, respectively. Patients with PD (n = 30) were included for discrimination. Twenty‐one participants had two scans. The principal component analysis was applied for pattern identification (DLB‐related pattern [DLBRP], PDD‐related pattern [PDDRP]). Similarities and differences among three patterns were assessed by pattern topography, pattern expression, clinical correlations cross‐sectionally, and pattern expression changes longitudinally. Results: DLBRP and PDDRP shared highly similar topographies, with relative hypometabolism mainly in the middle temporal gyrus, middle occipital gyrus, lingual gyrus, precuneus, cuneus, angular gyrus, superior and inferior parietal gyrus, middle and inferior frontal gyrus, cingulate, and caudate, and relative hypermetabolism in the cerebellum, putamen, thalamus, precentral/postcentral gyrus, and paracentral lobule, which were more extensive than the PDRP. Patients with DLB and PDD could not be distinguished successfully by any pattern, but patients with PD were easily recognized, especially by DLBRP and PDDRP. The pattern expression of DLBRP and PDDRP showed similar efficacy in cross‐sectional disease severity assessment and longitudinal progression monitoring. Conclusions: The consistent abnormalities in metabolic patterns of DLB and PDD might underline the potential continuum across the clinical spectrum from PD to DLB. © 2022 International Parkinson and Movement Disorder Society.